2010
DOI: 10.1111/j.1745-4514.2010.00366.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Content and Antioxidant Activity of Different Extracts From Ocimum Basilicum, Apium Graveolens and Lepidium Sativum Seeds

Abstract: The antioxidative properties and total phenolic contents of methanol, ethanol and water extracts from Ocimum basilicum, Apium graveolens and Lepidium sativum seeds were investigated and the results were compared with standards.The methanol extracts of the seeds had significantly higher (P < 0.05) superoxide radical scavenging activity with the concentration for 50% inhibition (IC 50 ) value of 98.73 mg/mL for O. basilicum, 121.57 mg/mL for A. graveolens and 166.16 mg/mL for L. sativum. The results indicated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 39 publications
4
36
1
Order By: Relevance
“…Obtained cana fistula IC 50 results are in agreement with [40] while lower values were reported by [41]. Basil obtained IC 50 results was better than previously reported by [42] who reported higher values. Mixing the two plant aqueous extracts affected positively by arising inhibition % and lowering mix IC 50 into (29.88 µg/mL).…”
Section: Hplc Phenolic Compounds Quantificationsupporting
confidence: 89%
“…Obtained cana fistula IC 50 results are in agreement with [40] while lower values were reported by [41]. Basil obtained IC 50 results was better than previously reported by [42] who reported higher values. Mixing the two plant aqueous extracts affected positively by arising inhibition % and lowering mix IC 50 into (29.88 µg/mL).…”
Section: Hplc Phenolic Compounds Quantificationsupporting
confidence: 89%
“…The major bioactive compounds detected in A. graveolens can include vitamins, minerals and a high amount of dietary fibers in addition to non‐nutrient chemicals such as a class of phenolic compounds (furanocoumarins, caffeic acid, ferulic acid, etc.) (Aydemir and Becerik ; Jung et al . ; Yao and Ren ; Baananou et al .…”
Section: Introductionmentioning
confidence: 99%
“…Whereas, flavonoid contents were higher in O. basilicum (18.16 mg QE/g, DW) as compared to L. royleana (16.03 mg QE/g, DW) (Figure ). According to Aydemir and Becerik (), total phenolic contents in O. basilicum ranged from 74 to 92 mg GAE/100 g in different solvent extracts. Variations in phenolic contents of different solvent extracts are attributed to polarities of different compounds present in seeds.…”
Section: Resultsmentioning
confidence: 97%
“…Amanzadeh, Dehaghi, Gohari, Monsef‐Esfahani, and Ebrahimi () analyzed the antioxidant activity of essential oil of L. iberica by DPPH radical scavenging assay and reported that essential oil of aerial parts showed the highest radical scavenging potential. Aydemir and Becerik () evaluated the antioxidant activity of different extracts from O. basilicum, Lepidium sativum, and Apium graveolens seeds and recorded 56.4% scavenging activity in methanolic extract of O. basilicum seeds at a concentration 250 μg/ml. In literature, antioxidant activity of O. basilicum leaves (60.75%) has also been reported by Zakaria, Aziz, Lachimanan, Sreenivasan, and Rathinam ().…”
Section: Resultsmentioning
confidence: 99%